Fiscal policy and private investment in less developed countries - Niels Hermes; Robert Lensink (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper analyses the impact of fiscal policy on private investment for a sample of thirty-three LDCs. The paper makes a number of important contributions to the existing empirical literature. Its main contribution is that it is the first attempt to analyse the existence of a non-linear relationship between fiscal policy variables and investment. Moreover, we explicitly focus on different aspects of fiscal policy and their influence on investment, instead of only looking at aggregate fiscal policy variables.
Keywords: O23; H30; 330; private investment; public investment; fiscal policy; LDCs; Investition; Finanzpolitik; Entwicklungsländer